2019
DOI: 10.1021/acschemneuro.9b00111
|View full text |Cite
|
Sign up to set email alerts
|

trans-Cinnamic Acid Conjugated Gold Nanoparticles as Potent Therapeutics against Brain-Eating Amoeba Naegleria fowleri

Abstract: Primary amoebic meningoencephalitis (PAM), a deadly brain infection, is caused by brain-eating amoeba Naegleria fowleri. The current first line of treatment against PAM is a mixture of amphotericin B, rifampin, and miltefosine. Since, no single effective drug has been developed so far, the mortality rate is above 95%. Moreover, severe adverse side effects are associated with these drugs. Nanotechnology has provided several advances in biomedical applications especially in drug delivery and diagnosis. Herein, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…As for the controls, the amoebae were incubated with Amphotericin B at 10 μM for the positive control; the 0.5% ethanol aqueous solution was used as solvent control, while untreated amoebae were considered as the negative control. 15 The Trypan blue exclusion staining as described in the Methods section was used to determine the number of viable cells. Viable cells were nonstained, while dead cells were stained blue.…”
Section: ■ Methodsmentioning
confidence: 99%
“…As for the controls, the amoebae were incubated with Amphotericin B at 10 μM for the positive control; the 0.5% ethanol aqueous solution was used as solvent control, while untreated amoebae were considered as the negative control. 15 The Trypan blue exclusion staining as described in the Methods section was used to determine the number of viable cells. Viable cells were nonstained, while dead cells were stained blue.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Amoebicidal and cytopathogenicity assays demonstrated anti-amoebic properties. Cinnamic acid exhibited low toxicity because of its plant origin compared to other biologically derived compounds [23]. Another current study showed that the AuNPs prevented HSV-1 infection by crossing BBB.…”
Section: Metal Nanoparticlesmentioning
confidence: 58%
“…CA-AuNp showed similar activity to AmB, which reduced the numbers of the amoeba to 1.6 × 10 5 . CA-AuNp showed no cytotoxicity towards Henrietta Lacks cervical cancer cells (HeLa) [ 86 ].…”
Section: Potential Treatmentmentioning
confidence: 99%